The putative forkhead transcription factor FOXL2 is mutated in blepharophimosis/ptosis/epicanthus inversus syndrome - Crisponi, Laura; Deiana, Manila; Loi, Angela; Chiappe, Francesca; Uda, Manuela; Amati, Patrizia; Bisceglia, Luigi; Zelante, Leopoldo; Nagaraja, Ramaiah; Porcu, Susanna; Serafina Ristaldi, M.; Marzella, Rosalia; et al. (Nature genetics, 2001)
In type I blepharophimosis/ptosis/epicanthus inversus syndrome (BPES), eyelid abnormalities are associated with ovarian failure. Type II BPES shows only the eyelid defects, but both types map to chromosome 3q23. We have positionally cloned a novel, putative winged helix/forkhead transcription factor gene, FOXL2 , that is mutated to produce truncated proteins in type I families and larger proteins in type II. Consistent with an involvement in those tissues, FOXL2 is selectively expressed in the mesenchyme of developing mouse eyelids and in adult ovarian follicles; in adult humans, it appears predominantly in the ovary. FOXL2 represents a candidate gene for the polled/intersex syndrome XX sex-reversal goat.